PENANGANAN SAMPAH ORGANIK DENGAN TONG SAMPAH KOMPOSTER DI DESA KARANGCANGKRING KECAMATAN DUKUN KABUPATEN GRESIK (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
The garbage which is not properly to manage will impact the health, social and economic which can be impact some problems in Karangcangkring village, Dukun district Gresik regency. Most of residents in Gresik are still throwing garbage in any places and make puddles for landfills. This paper focuses on some issues of handling organic waste from the initially discarded in places and wallow carelessly processed into compost and liquid fertilizer in a composter in Dukun district, Gresik regency. The activities begin with making management team that are divided according to their respective of their village, provision of trash for inorganic waste, manufacture and operation of the composter training for the management team, training provision and operation of the composter for residents. The results of activities undertaken Karangcangcangkring village has a system to manage garbage, produce fertilizer, so the impact will improve the quality of health and social citizens.